Factory production control for CE marking on construction product / Nik Hasmawati Nik Din - Nik Din, Nik Hasmawati (2006)
Effective from 1April 2004, panel products intended for European market have to bear the CE Marking. For the manufacturer to conform to the marking, factory production control (FPC) system is necessary to be set up at all levels of attestation of conformity. This project describes the requirements of FPC and highlights the specific characteristics performances to be considered and verified for panel products.